Sistem Kendali dan Monitoring Infus Berbasis Internet of Things - Firmansyah MSN; Azis Muhajar; Abdul Chobir; Andri Ulus Rahayu (Politeknik Negeri Batam, 2022)
Intravenous therapy is a way to give fluids into the body through a vein to replace lost fluids. Problems that occur with the use of intravenous therapy include air embolism or blood rising into the infusion tube, the number of drops is not as needed, and the infusion volume vacancy, if not treated quickly, will cause blood to rise to the infusion tube. Monitoring and regulation of infusion drops can be done automatically, using the SG90 servo motor, photodiode sensors and internet of things technology, using the MQTT protocol as a communication protocol that is capable of sending data in real-time. This study makes a device that is able to detect bubbles and blood in the infusion tube, adjust the infusion drip automatically with an average drop per minute error of 2.67% at 20 DPM set point and 1.67% at 60 DPM set point, and speed the average data transmission to the server is 0.134 seconds with WIFI signal strength between -62.2 dB to -85.4 dB.